Cytogenetic risk stratification in chronic myelomonocytic leukemia - Esperanza Such; J. Cervera; Dolors Costa; Françesc Solé; Teresa Vallespı́; Elisa Luño; Rosa Collado; Marı́a José Calasanz; Jesús María Hernández‐Rivas; Juan C. Cigudosa; Benet Nomdedeu; Mar Mallo; et al. (2010)
Background The prognostic value of cytogenetic findings in chronic myelomonocytic leukemia is unclear. Our purpose was to evaluate the independent prognostic impact of cytogenetic abnormalities in a large series of patients with chronic myelomonocytic leukemia included in the database of the Spanish Registry of Myelodysplastic Syndromes.Design and Methods We studied 414 patients with chronic myelomonocytic leukemia according to WHO criteria and with a successful conventional cytogenetic analysis at diagnosis. Different patient and disease characteristics were examined by univariate and multivariate methods to establish their relationship with overall survival and evolution to acute myeloid leukemia.Results Patients with abnormal karyotype (110 patients, 27%) had poorer overall survival (P=0.001) and higher risk of acute myeloid leukemia evolution (P=0.010). Based on outcome analysis, three cytogenetic risk categories were identified: low risk (normal karyotype or loss of Y chromosome as a single anomaly), high risk (presence of trisomy 8 or abnormalities of chromosome 7, or complex karyotype), and intermediate risk (all other abnormalities). Overall survival at five years for patients in the low, intermediate, and high risk cytogenetic categories was 35%, 26%, and 4%, respectively (P